Implementasi Program One Day One Ayat dan Program Murojaah Untuk Meningkatkan Kecerdasan Spiritual Santri Tingkat Smp Ypds (Yayasan Pendidikan Dan Sosial) Nurul Falah Mojokerto Tahun Ajaran 2022-2023 - Vivi Ning Alami; Muhammad Ahmad Fulka Sa’dibih (Amaliyatu Tadris (AMYTA), 2023)
One Day One Ayat is an alternative program designed to cultivate students’ habits of involving the Qur’an in their daily lives. The One Day One Ayat method is a Qur’anic memorization approach in which students memorize one verse per day. However, this method emphasizes not only memorization of the verse, but also understanding its meaning and, most importantly, practicing its values in daily life. The focus of this study includes: (1) the stages of the One Day One Ayat program in improving students’ spiritual intelligence; (2) the stages of the murojaah program in improving students’ spiritual intelligence; and (3) the supporting factors in the implementation of the One Day One Ayat and murojaah programs. The purpose of this study is to describe the stages of the One Day One Ayat and murojaah programs in enhancing the spiritual intelligence of junior high school students at YPDS Nurul Falah Mojokerto in the 2022/2023 academic year. To identify the research problems, this study employed a qualitative approach using a case study design. Data were collected through unstructured interviews, non-participant observation, and documentation. Data analysis was conducted through data condensation, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The results of this study show that the implementation of the One Day One Ayat and murojaah programs in improving students’ spiritual intelligence at YPDS Nurul Falah Mojokerto in the 2022/2023 academic year consists of three stages. First, the planning stage of the One Day One Ayat program, which includes placement tests, meetings to improve student quality in the One Day One Ayat program, setting program targets, and determining program objectives. Second, the implementation stage of the One Day One Ayat and murojaah programs, which includes the learning process and the improvement of students’ spiritual intelligence. Third, the evaluation stage of the One Day One Ayat and murojaah programs, which involves assessments to determine students’ eligibility for advancement to the next level, identification of obstacles in implementing the programs, and evaluation of the outcomes of the One Day One Ayat and murojaah programs. The supporting factors for the implementation of the One Day One Ayat and murojaah programs in improving students’ spiritual intelligence include: (1) environmental conditions that support the implementation of the programs; (2) organizational relationships among parties involved in the One Day One Ayat and murojaah program activities; and (3) the availability of resources for the One Day One Ayat and murojaah programs. One Day One Ayat merupakan salah satu alternative untuk melatih kebiasaan peserta didik untuk melibatkan Al-Qur’an dalam setiap urusannya. Metode One Day One Ayat adalah metode menghafal Al-Qur’an satu hari satu ayat. Satu hari satu ayat bukan hanya ayatnya yang kita hafal, namun lebih dari itu. Artinya kandungannya dan yang terpenting adalah mengamalkanny. Fokus yang dikaji dalam peneliti ini yaitu: 1) Tahapan program One Day One Ayat dalam meningkatkan kecerdasan spiritual santri 2) Tahapan program murojaah dalam meningkatkan kecerdasan spiritual santri 3) Faktor-faktor pendukung implementasi program One Day One Ayat dan program murojaah. Tujuan penelitian adalam mendeskripsikan tahapan program One Day One Ayat dan program murojaah untuk meningkatkan kecerdasan spiritual santri tingkat SMP YPDS Nurul Falah Mojokerto Tahun Pelajaran 2022/2023. Untuk mengidentifikasi permasalahan tersebuat, pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dan jenis penelitian studi kasus. Teknik pengumpulan data menggunakan wawancara tidak terstruktur, observasi nonpartisipasi dan dokumentasi. Analisis data menggunakan kondensasi data, penyajian data dan kesimpulan. Keabsahan data dalam penelitian ini menggunakan triangulasi sumber dan triangulasi Teknik. Hasil dari penelitian ini yaitu: Bagaimana tahapan program One Day One Ayat dan program murojaah untuk meningkatkan kecerdasan spiritual santri tingkat SMP YPDS Nurul Falah Mojokerto tahun pelajaran 2022/2023. Yaitu pertama, perencanaan program One Day One Ayat, dalam perencanaan ada tes pengelompokan, rapat peningkatan kualitas peserta didik pada program One Day One Ayat, target program One Day One Ayat dan tujuan program One Day One Ayat. Kedua, pelaksanaan program One Day One Ayat dan program murojaah, dalam pelaksanaan ada proses pembelajaran, dan meningkatnya kecerdasan spiritual peserta didik. Ketiga, evaluasi program One Day One Ayat dan program murojaah dalam evaluasi ada tes untuk kelayakan peserta didik naik kejenjang berikutnya, kendala para program One Day One Ayat dan program murojaah dan hasil dari program One Day One Ayat dan program murojaah.Bagaimana faktor-faktor pendukung implementasi program One Day One Ayat dan program murojaah untuk meningkatkan kecerdasan spiritual santri tingkat SMP YPDS Nurul Falah Mojokerto tahun pelajaran 2022/2023. Yaitu pertama kondisi lingkungan dalam pelaksanaan program One Day One Ayat dan program murojaah. Kedua hubungan antar organisasi kegiatan program One Day One Ayat dan program murojaah, dan ketiga sumberdaya program One Day One Ayat dan program murojaah